Effect of different synthesis methods on the textural properties of calcium tungstate (CaWO4) and its catalytic properties in the toluene oxidation - Da Silva Alencara, Lorena Dariane; Lima, Naiara Arantes; Mesquita, Alexandre [UNESP]; Probst, Luiz Fernando Dias; Batalha, Daniel Carreira; Rosmaninho, Marcelo Gonçalves; Fajardo, Humberto Vieira; Balzer, Rosana; Bernardi, Maria Inês Basso (FapUNIFESP (SciELO), 2018)
Calcium tungstate (CaWO4) crystals were prepared by microwave-assisted hydrothermal (MAH) and polymeric precursor methods (PPM). These crystals were structurally characterized by X-ray diffraction (XRD), N2 adsorption, X-ray absorption near edge spectroscopy (XANES) and extended X-ray absorption fine structure (EXAFS) measurements. The morphology and size of these crystals were observed by field emission scanning electron microscopy (FESEM). Their optical properties were investigated by ultraviolet visible (UV-Vis) absorption and photoluminescence (PL) measurements. Moreover, these materials were employed as catalysts towards gas phase toluene oxidation reaction. XRD indicates the purity of materials for both preparation methods and MAH process produced crystalline powders synthesized at lower temperatures and shorter processing time compared to the ones prepared by PPM. FESEM images showed particles with rounded morphology and particles in clusters dumbbellslike shaped. PL spectra exhibit a broad band covering the visible electromagnetic spectrum in the range of 360 to 750 nm. XANES and EXAFS results show that preparation method does not introduce high disorders into the structure, however the H2-TPR results indicated that the catalyst reducibility is affected by the preparation method of the samples.
Keywords: CaWO4; EXAFS; H2-TPR; Toluene; XANES